Mindfulness for people with chronic pain: Factors affecting engagement and suggestions for programme optimisation - Fathima L. Marikar Bawa; Stewart W. Mercer; Jane W. Sutton; Christine M. Bond (Wiley, 2023)
Abstract Introduction Chronic pain is a common, multifactorial condition and pharmacological treatments have limited benefits. Mindfulness is a holistic approach that might be of value in the management of chronic pain. However, attrition rates from mindfulness‐based interventions are high and factors affecting engagement are unknown. The aim of this study was to inform the design of a mindfulness programme that would be accessible and acceptable for people with chronic pain. Methods Interpretative phenomenological analysis of interview data from people with chronic pain who had taken part in an 8‐week mindfulness programme based on mindfulness‐based stress reduction revealed factors affecting engagement with and suggestions for tailoring the programme. Factors were grouped into physical, psychological and social domains. Further suggestions for tailoring the programme to address these factors were generated through a nominal group of healthcare professionals and a focus group with service users who had chronic pain. Findings Physical factors included disability and discomfort with some practices; psychological factors included expectations of the mindfulness programme and understanding the relationship between mindfulness and pain; and social factors included loneliness and support from others. The proposed modifications to the mindfulness programme supported by healthcare professionals and/or service users to address these are described in this paper. Public Contribution This study involved public contributions at a number of stages. The University of Aberdeen Division of Applied Health Sciences Service User Group (who were members of the public with chronic pain) was involved in the design of the study. Patients with chronic pain recruited from general medical practice who took part in the mindfulness programme were interviewed on their experience of the programme. Patients with chronic pain who attended the mindfulness programme, and healthcare professionals with expertise in chronic pain and/or mindfulness, attended meetings to design a tailored mindfulness programme for people with chronic pain.